Germination Ecology of Two Troublesome Weeds of Arid Chickpea: Euphorbia dracunculoides and Astragalus Species - IKRAM,R.M. (2019)
ABSTRACT: The species Euphorbia dracunculoides and Astragalus are problematic weeds of arid chickpea in the chickpea mono-cropping system in Pakistan. The influence of various ecological factors on germination and seedling emergence characteristics of these weeds was determined under laboratory conditions. The results suggested that seed germination of both species was 50% at 15 oC under light conditions, and germination decreased when the temperature was increased. The increase in drought stress from 2.5 to 15% significantly decreased germination of E. dracunculoides and Astragalus spp. Both species failed to germinate at the osmotic potential of -3.02 MPa. The increase in field capacity from 25 to 100% increased emergence percentage and emergence index of both weeds. A pH range of 6 to 9 did not influence seed germination of both species and they were able to germinate at a wide range of pH conditions. Both weeds were very sensitive to salinity; however, a few seeds (10%) of Astragalusspp. germinated even at a 150 mM sodium chloride concentration. To check the effect of burial depth, seeds were placed in pots under seeding depths of 0 to 6 cm at an interval of 1 cm, respectively. Maximum emergence was attained at the soil surface and emergence declined with increasing depths. Seedling emergence of E. dracunculoides was higher than that of Astragalusspp. at all burial depths. Studies on germination ecology of these two weeds will offer insights into their behavior under different environmental conditions. Their germination responses and growth patterns under different ecological factors will help us to design an efficient management strategy to control these two troublesome weeds.